The Effect Of Human Resources Capacity, Use Of Information Technology, and Internal Control Systems on Reliability and Timeliness of Financial Statements Submission (Empirical Evidence from Pekanbaru City Regional Organization) - Murni, Fina; Indrawati, Novita; Desmiyawati, Desmiyawati (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to examine the effect of human resource capacity, utilization of information and technology, and internal control on reliability and timeliness of financial reporting. Using a sample of 129 respondents from organization of Regional Device in Pekanbaru Region. The hypotheses testing with multiple analysis regression and the statistical program that used is SPSS 25. Our findings show that human resource, utilization of information and technology, and internal control system are positive significantly the reliability and timeliness of financial reporting.